Positive electrode material and preparation method thereof, positive electrode plate, battery and electric device
Through mechanical fusion, the inner core material of the layered oxide is fused with the outer polyanionic cladding material to form a composite core-shell structure, solving the stability and capacity problems of the positive electrode materials of the existing sodium ion battery and achieving efficient ion transport and cycling performance.
Patent Information
- Application Number
- CN202411799091.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-07
- Publication Date
- 2025-03-07
AI Technical Summary
The existing sodium ion battery positive electrode materials are prone to impurities during the preparation process, resulting in reduced capacity and poor conductivity. The layered oxide-based materials are easily affected by environmental moisture and have poor stability.
Through mechanical fusion, the inner core material of the layered oxide is fused with the outer polyanionic cladding material to form a composite core-shell structure. The polyanionic outer cladding material includes sodium manganese phosphate pyrophosphate, which forms a bilayer structure with the inner core material of the layered oxide to enhance ion transport characteristics and improve stability.
It improves the circulation performance and environmental stability of the cathode material, reduces the dissolution of manganese and the Jahn-Teller effect, maintains a high energy density, and is suitable for use in sodium ion batteries.
Smart Images

Figure CN119581537A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of material chemistry, and in particular to positive electrode materials and preparation methods thereof, positive electrode sheets, batteries and electrical devices. Background Art
[0002] With the development of science and technology and the progress of the times, the problems of energy shortage and environmental degradation have gradually emerged before people. In order to cope with the energy crisis, the development of renewable energy such as wind energy, solar energy, tidal energy, or new and efficient energy storage devices has become a hot topic of research. At present, lithium-ion batteries with relatively mature commercial applications are difficult to meet the growing commercial demand due to the small reserves of lithium metal in the earth. As an alkali metal element in the same main group as lithium, sodium is very similar to lithium in physical and chemical properties. In addition, sodium is abundant in reserves and its price is much lower than that of metallic lithium. It can be used as a new generation of electrochemical secondary batteries. Compared with lithium-ion batteries, sodium-ion batteries are more suitable as devices for large-scale energy storage. As the price of raw materials for lithium-ion batteries rises, sodium-ion batteries may become an important supplement to lithium-ion batteries. Compared with lithium-ion batteries, sodium-ion batteries have obvious advantages in cost and charging time. The charging time of lithium iron phosphate batteries is longer, about 45 minutes; while the charging time of sodium-ion batteries only takes 10 minutes, which provides a direction for solving the problem of long charging time for electric vehicles.
[0003] Polyanion-based sodium ion battery cathode materials have the advantages of stable structure, high safety, and open sodium ion transmission channels; however, during the preparation of the materials, impurities are easily generated, resulting in reduced capacity and poor conductivity. Layered oxide-based sodium ion battery cathode materials have higher capacity and excellent rate performance than polyanion-based sodium ion battery cathode materials, but layered oxide-based sodium ion battery cathode materials are easily affected by moisture in the environment, have poor stability, and suffer severe capacity decay during the cycle. How to solve the above problems is what technicians in this field need to consider. Summary of the invention
[0004] To solve the problems in the prior art, the embodiments of the present application provide positive electrode materials and preparation methods thereof, positive electrode sheets, batteries and electrical devices.
[0005] The present invention provides a method for preparing a positive electrode material, which comprises the following steps:
[0006] preparing a layered oxide internal core material, wherein the layered oxide internal core material is a layered oxide containing sodium and a transition metal;
[0007] preparing a polyanion system external coating material, wherein the polyanion system external coating material comprises sodium manganese ferrophosphate pyrophosphate;
[0008] The inner core material of the layered oxide and the outer coating material of the polyanion system are fused by mechanical fusion to obtain a positive electrode material having a core-shell structure of a composite of the layered oxide and the polyanion.
[0009] In one embodiment, the steps of preparing the layered oxide internal core material include:
[0010] A certain amount of sodium source is added to the metal hydroxide precursor, mixed evenly and then sintered;
[0011] The sintered material is crushed and sieved to obtain the layered oxide internal core material.
[0012] In one embodiment, the chemical formula of the metal hydroxide precursor is M(OH)2,
[0013] Wherein, M includes at least one of Fe, Ni, Cu, Zn, Co, Ti, and Mn, the sodium source includes one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, and sodium acetate, the molar ratio of Na element to M in the metal hydroxide precursor is 1.2:1 to 0.8:1, the temperature range of the sintering process is 800°C to 1200°C, and the sintering time of the sintering process is 10 hours to 20 hours.
[0014] In one embodiment, the steps of preparing the polyanion-based external coating material include:
[0015] Mixing an iron source, a sodium source, a phosphorus source, a carbon source, and citric acid in a solvent to form a solution;
[0016] The solution is placed in a resistance furnace for heating, the temperature range of the resistance furnace is 200° C. to 600° C., and ultrasound of 20 kHz to 100 kHz is applied to the solution to make the solution boil, evaporate, condense and burn, so as to obtain a precursor powder;
[0017] The precursor powder is sintered in an inert gas atmosphere, and then pulverized to obtain the polyanion-based external coating material.
[0018] In one embodiment, the iron source includes one or more of ferrous oxalate, ferric nitrate, and ferric sulfate; the phosphorus source includes one or more of ferric phosphate, diammonium phosphate, sodium phosphate, sodium dihydrogen phosphate, phosphoric acid, sodium pyrophosphate, sodium dihydrogen pyrophosphate, and diammonium pyrophosphate; the sodium source includes one or more of sodium carbonate, sodium hydroxide, sodium bicarbonate, sodium dihydrogen phosphate, sodium acetate, and sodium oxalate; the carbon source includes one or more of glucose, sucrose, polyethylene glycol, citric acid, oxalic acid, carbon nanotubes, and graphite; and the solvent includes one or more of deionized water and anhydrous ethanol.
[0019] In one embodiment, the temperature range for sintering the precursor powder is 300°C to 800°C, the sintering time is 6 hours to 12 hours, the inert gas includes one or more of nitrogen, helium, and argon, and the oxygen concentration is less than or equal to 20 ppm; the particle size D50 of the polyanion-based external coating material is in the range of 50nm to 300nm, and the specific surface area range BET of the polyanion-based external coating material is 10㎡ / g to 20㎡ / g.
[0020] In one embodiment, the step of fusing the layered oxide inner core material and the polyanion outer coating material by mechanical fusion comprises:
[0021] Weighing the layered oxide inner core material and the polyanion outer coating material to obtain a mixture, wherein the mass proportion of the polyanion outer coating material is less than or equal to 30%;
[0022] The mixture is placed in a mechanical fusion machine and stirred to mix evenly. The rotation speed range of the mechanical fusion machine is 2000 rpm to 10000 rpm, and the stirring time is 3 minutes to 10 minutes. The mechanical fusion machine is equipped with zirconium balls to crush and extrude the mixture to obtain the positive electrode material having a core-shell structure composite of layered oxides and polyanions.
[0023] The present application also provides a positive electrode material, which is prepared by the positive electrode material preparation method described in any one of the above embodiments, and the positive electrode material includes the layered oxide internal core material and the polyanion system external coating material;
[0024] The layered oxide internal core material includes Na 1+x MO2, wherein -0.3≤X≤0.2, M comprises at least one of Fe, Ni, Cu, Zn, Co, Ti, and Mn;
[0025] The polyanion system external coating material includes Na4Fe 3-y Mn y (PO4)2P2O7 / C.
[0026] An embodiment of the present application also provides a battery, the battery comprising a positive electrode, the positive electrode comprising a positive electrode material prepared by the method for preparing the positive electrode material described in any one of the aforementioned embodiments, or the positive electrode comprising the positive electrode material as described in the aforementioned embodiments.
[0027] An embodiment of the present application also provides an electrical device, which includes an electrical main body and a battery, wherein the battery includes a positive electrode, and the positive electrode includes a positive electrode material prepared by the method for preparing the positive electrode material described in any one of the aforementioned embodiments, or the positive electrode includes the positive electrode material described in the aforementioned embodiments.
[0028] Furthermore, the positive electrode material and preparation method thereof, positive electrode plate, battery and power-consuming device of the present application coat the polyanion system external coating material on the surface of the layered oxide internal core material; the polyanion system external coating material belongs to metal phosphate, and it can enhance the ion transport characteristics by coating the layered oxide internal core material as a coating layer. The polyanion system external coating material increases ion diffusion by forming a double-layer structure with the layered oxide internal core material, reduces the dissolution of manganese and reduces the Jahn-Teller effect, improves its disadvantage of poor environmental stability, and improves cycle performance. Compared with traditional coating materials (such as nano-metal oxides and carbon materials), the polyanion-based external coating material itself is an active substance with a certain specific capacity, and will not reduce the energy density of the positive electrode material too much; at the same time, compared with general polyanion-based materials (such as sodium ferric pyrophosphate), sodium manganese ferric pyrophosphate is doped with manganese, which improves the voltage platform of the polyanion-based external coating material and improves the disadvantage of the low voltage platform of the polyanion-based material, making the voltage platform of the polyanion-based external coating material closer to the internal core material of the coated layered oxide, which helps to improve the overall voltage platform of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is the 1C cycle capacity retention rate of NFM / NFPP-1, NFM / NFPP-2, NFM / NFPP-3, and NFM / NFPP-4 in the examples of the present application.
[0030] Figure 2 0.1C charge and discharge curves of NFM / NFPP-1, NFM / NFPP-2, NFM / NFPP-3, and NFM / NFPP-4 in the examples of the present application.
[0031] Figure 3 Schematic diagram of scanning electron microscopy of NFM / NFPP-1 in the examples of the present application.
[0032] Figure 4 Schematic diagram of scanning electron microscopy of NFM / NFPP-4 in the examples of the present application.
[0033] Figure 5 Schematic diagram of scanning electron microscopy of NFM / NFPP-5 in the examples of the present application.
[0034] Figure 6The following specific implementation will further illustrate the present application in conjunction with the above-mentioned figures. DETAILED DESCRIPTION
[0035] The following description will refer to the accompanying drawings to more fully describe the content of the present application. Shown in the accompanying drawings are exemplary embodiments of the present application. However, the present application can be implemented in many different forms and should not be construed as being limited to the exemplary embodiments set forth herein. These exemplary embodiments are provided to make the present application thorough and complete, and to fully convey the scope of the present application to those skilled in the art. Similar reference numerals represent identical or similar components.
[0036] The terms used herein are only used for the purpose of describing specific exemplary embodiments and are not intended to limit the present application. As used herein, unless the context clearly indicates otherwise, the singular forms "a", "an" and "the" are intended to also include the plural forms. In addition, when used herein, "including" and / or "comprising" and / or "having", integers, steps, operations, components and / or components, but do not exclude the existence or addition of one or more other features, regions, integers, steps, operations, components and / or groups thereof.
[0037] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those of ordinary skill in the art to which this application belongs. In addition, unless explicitly defined herein, terms such as those defined in general dictionaries should be interpreted as having a meaning consistent with their meaning in the relevant technology and the content of this application, and will not be interpreted as an idealized or overly formal meaning.
[0038] The specific implementation methods of the present application are further described in detail below with reference to the accompanying drawings.
[0039] The present invention provides a method for preparing a positive electrode material, which comprises the following steps:
[0040] preparing a layered oxide internal core material, wherein the layered oxide internal core material is a layered oxide containing sodium and a transition metal;
[0041] preparing a polyanion system external coating material, wherein the polyanion system external coating material comprises sodium manganese ferrophosphate pyrophosphate;
[0042] The inner core material of the layered oxide and the outer coating material of the polyanion system are fused by mechanical fusion to obtain a positive electrode material having a core-shell structure of a composite of the layered oxide and the polyanion.
[0043] In one embodiment, the method for preparing the positive electrode material provided in the embodiment of the present application comprises the following steps:
[0044] Step S1: preparing a layered oxide internal core material, wherein the layered oxide internal core material is a layered oxide containing sodium and a transition metal.
[0045] In one embodiment, step S1 includes:
[0046] Step S11: adding a certain amount of sodium source into the metal hydroxide precursor, mixing evenly and then sintering.
[0047] In one embodiment, the chemical formula of the metal hydroxide precursor is M(OH)2, wherein M includes at least one of Fe, Ni, Cu, Zn, Co, Ti, and Mn.
[0048] In this embodiment, when M includes multiple elements at the same time, the sum of the moles of the multiple elements is 1.
[0049] In one embodiment, the sodium source includes one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, and sodium acetate, and the molar ratio of the Na element to M in the metal hydroxide precursor is 1.2:1 to 0.8:1.
[0050] In this embodiment, the molar ratio of the Na element to the M in the metal hydroxide precursor may be 1.1:1, 1:1 and 0.9:1. After the metal hydroxide precursor and the Na source are mixed, they may be mixed uniformly by high-speed mixing.
[0051] Step S12: crushing and screening the sintered material to obtain the layered oxide internal core material.
[0052] In one embodiment, the temperature range of the sintering process is 800° C. to 1200° C., and the sintering time of the sintering process is 10 hours to 20 hours.
[0053] In this embodiment, the temperature of the sintering process can be 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C, 950°C, 960°C, 970°C, 980°C, 990°C, 1000°C, 1010°C, 1020°C, 1030°C, 1040°C, 1050°C, 1060°C, 1070°C, 1080°C, 1090°C, 1100°C, 1110°C, 1120°C, 1130°C, 1140°C, 1150°C, 1160°C, 1170°C, 1180°C, 1190°C. The heating rate of the sintering process is 3°C / min. The sintering time of the sintering process can specifically be 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, or 19 hours.
[0054] In one embodiment, the sintering process uses one or more of dry air or oxygen.
[0055] Step S2: preparing a polyanion-based external coating material, wherein the polyanion-based external coating material comprises sodium manganese ferric pyrophosphate.
[0056] In one embodiment, step S2 includes:
[0057] Step S21: Mix an iron source, a sodium source, a phosphorus source, a carbon source, and citric acid in a solvent to form a solution.
[0058] In one embodiment, the iron source includes one or more of ferrous oxalate, ferric nitrate, and ferric sulfate.
[0059] In one embodiment, the phosphorus source includes one or more of ferric phosphate, ammonium dihydrogen phosphate, sodium phosphate, sodium dihydrogen phosphate, phosphoric acid, sodium pyrophosphate, sodium dihydrogen pyrophosphate, and ammonium dihydrogen pyrophosphate.
[0060] In one embodiment, the sodium source includes one or more of sodium carbonate, sodium hydroxide, sodium bicarbonate, sodium dihydrogen phosphate, sodium acetate, and sodium oxalate.
[0061] In one embodiment, the carbon source includes one or more of glucose, sucrose, polyethylene glycol, citric acid, oxalic acid, carbon nanotubes, and graphite.
[0062] In one embodiment, the solvent includes one or more of deionized water and anhydrous ethanol.
[0063] In one embodiment, the slurry solid content of the solution can range from 30% to 50%. In this embodiment, the slurry solid content of the solution can also be 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%.
[0064] Step S22: placing the solution in a resistance furnace for heating, the temperature range of the resistance furnace is 200° C. to 600° C., and applying ultrasound of 20 khz to 100 khz to the solution to make the solution boil, evaporate, condense and burn to obtain a precursor powder.
[0065] In one embodiment, after the solution is placed in a resistance furnace, an ultrasonic probe may be inserted into the solution to apply ultrasound to the solution, and the solution may be boiled, evaporated, concentrated and burned under the action of the ultrasonic field and the temperature field to obtain a fluffy precursor powder.
[0066] In this embodiment, the ultrasonic parameters applied may be 25khz, 30khz, 35khz, 40khz, 45khz, 50khz, 55khz, 60khz, 65khz, 70khz, 75khz, 80khz, 85khz, 90khz, 95khz, and preferably 40khz.
[0067] It is understandable that the mechanical effect and cavitation effect of ultrasound can not only promote the reaction, but also effectively prevent the particles from agglomerating and growing by applying an ultrasonic environment to the reaction process. At the same time, the introduction of ultrasound factors into the reaction process can transform the block agglomerates formed by the traditional synthesis method into a three-dimensional (3D) network structure rich in holes, and can also reduce the size of the material grains.
[0068] In this embodiment, the temperature of the resistance furnace can be 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C,
[0069] 320℃、330℃、340℃、350℃、360℃、370℃、380℃、390℃、400℃、
[0070] 410℃、420℃、430℃、440℃、450℃、460℃、470℃、480℃、490℃、
[0071] 500℃、510℃、520℃、530℃、540℃、550℃、560℃、570℃、580℃、
[0072] 590℃.
[0073] Step S23: sintering the precursor powder in an inert gas atmosphere, and crushing the precursor powder after sintering to obtain the polyanion-based external coating material.
[0074] In one embodiment, the temperature range of sintering the precursor powder is 300° C. to 800° C., and the sintering time is 6 hours to 12 hours.
[0075] In this embodiment, the temperature for sintering the precursor powder can be 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C,
[0076] 400℃、410℃、420℃、430℃、440℃、450℃、460℃、470℃、480℃、
[0077] 490℃、500℃、510℃、520℃、530℃、540℃、550℃、560℃、570℃、
[0078] 580℃、590℃、600℃、610℃、620℃、630℃、640℃、650℃、660℃、
[0079] 670℃、680℃、690℃、700℃、710℃、720℃、730℃、740℃、750℃、
[0080] 760℃, 770℃, 780℃, 790℃.
[0081] In one embodiment, the inert gas includes one or more of nitrogen, helium, and argon, and the oxygen concentration is less than or equal to 20 ppm.
[0082] In one embodiment, the particle size D50 of the polyanionic external coating material is in the range of 50 nm to 300 nm, and the specific surface area BET of the polyanionic external coating material is in the range of 10 m2 / g to 20 m2 / g.
[0083] In this embodiment, the particle size D50 of the polyanion-based external coating material can specifically be 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, 210nm, 220nm, 230nm, 240nm, 250nm, 260nm, 270nm, 280nm, or 290nm.
[0084] In this embodiment, the specific surface area range BET of the polyanion-based external coating material can be 11 m2 / g, 12 m2 / g, 13 m2 / g, 14 m2 / g, 15 m2 / g, 16 m2 / g, 17 m2 / g, 18 m2 / g, and 19 m2 / g.
[0085] Step S3: fusing the inner core material of the layered oxide and the outer coating material of the polyanion system by mechanical fusion to obtain a positive electrode material having a core-shell structure of a composite of the layered oxide and the polyanion.
[0086] It can be understood that there is no distinction between the order of step S1 and step S2.
[0087] In one embodiment, step S3 includes:
[0088] Step S31: weighing the layered oxide internal core material and the polyanion system external coating material to obtain a mixture, wherein the mass proportion of the polyanion system external coating material is less than or equal to 30%.
[0089] In this embodiment, the mass proportion of the polyanion-based external coating material can be 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, or 29%.
[0090] Step S32: Place the mixture into a mechanical fusion machine and stir to mix evenly. The rotation speed range of the mechanical fusion machine is 2000 rpm to 10000 rpm, and the stirring time is 3 minutes to 10 minutes. The mechanical fusion machine is equipped with zirconium balls to crush and extrude the mixture to obtain the positive electrode material having a core-shell structure of a composite of layered oxides and polyanions. Cooling water can be used for cooling during the stirring process.
[0091] In this embodiment, the speed of the mechanical fusion machine can be 2100rpm, 2200rpm, 2300rpm, 2400rpm, 2500rpm, 2600rpm, 2700rpm, 2800rpm, 2900rpm, 3000rpm, 3100rpm, 3200rpm, 3300rpm, 3400rpm, 3500rpm, 3600rpm, 3700rpm, 3800rpm, 3900rpm, 4000rpm, 5100rpm, 5200rpm, 5300rpm, 5400rpm, 5500rpm, 5600rpm, 5700rpm, 5800rpm, 5900rpm, 6000rpm, 6100rpm, 6200rpm, 6300rpm, 6400rpm 900rpm, 6000rpm, 7100rpm, 7200rpm, 7300rpm, 7400rpm, 7500rpm, 7600rpm, 7700rpm, 7800rpm, 7900rpm, 8000rpm, 8100rpm, 8200rpm, 8300rpm, 8400 rpm, 8500rpm, 8600rpm, 8700rpm, 8800rpm, 8900rpm, 9000rpm, 9100rpm, 9200rpm, 9300rpm, 9400rpm, 9500rpm, 9600rpm, 9700rpm, 9800rpm, 9900rpm.
[0092] It can be understood that the layered oxide inner core material and the polyanion outer coating material are placed in a mechanical fusion machine, and pressure is applied while being stirred and mixed at high speed. The powerful shearing, collision, crushing and extrusion forces of the zirconium balls moving at high speed in the stirring tank are used to crush the polycrystalline spherical polyanion outer coating material into nano-scale single crystal primary particles, and the particles are coated and combined with the single crystal layered oxide inner core material by centrifugation and extrusion. - , and has a positive charge; while Na4Fe 3-x Mn x (PO4)2P2O7 / C (polyanion system external coating material) contains phosphate and is negatively charged; the layered oxide internal core material and the polyanion system external coating material are firmly bonded to each other through Coulomb electrostatic attraction. At the same time, the carbon black coated on the surface of the polyanion system external coating material adsorbs oxygen, hydrogen, hydroxyl, carboxyl and other functional groups, which will bond with the -OH on the surface of the layered oxide internal core material to form a bond, making the nanoscale Na4Fe 3-x Mn x (PO4)2P2O7 / C is more tightly embedded in the surface of the core material inside the layered oxide, and the two substances are evenly fused together to obtain the positive electrode material.
[0093] An embodiment of the present application also provides a positive electrode material, which is prepared by the positive electrode material preparation method described in any one of the above embodiments, and the positive electrode material includes the layered oxide internal core material and the polyanion system external coating material.
[0094] In one embodiment, the layered oxide inner core material comprises Na 1+x MO2, wherein -0.3≤X≤0.2, M comprises at least one of Fe, Ni, Cu, Zn, Co, Ti, and Mn; the polyanion system external coating material comprises Na4Fe 3-y Mn y (PO4)2P2O7 / C.
[0095] The present application also provides a battery, comprising a positive electrode, wherein the positive electrode comprises a positive electrode material prepared by the method for preparing a positive electrode material described in any one of the above embodiments, or the positive electrode comprises the positive electrode material described in the above embodiments.
[0096] In one embodiment, the present application also includes a method for making and testing the electrochemical performance of a sodium ion battery button cell, comprising the following steps: weighing 9g of the prepared positive electrode material, 0.5g of conductive carbon black, and 5g of a binder (polyvinylidene fluoride-NMP solution, solid content 10%) in a mass ratio of 9:0.5:0.5, stirring and dispersing them in an N-methylpyrrolidone solvent, stirring the obtained mixed slurry in a planetary ball mill for 90 minutes, and then evenly coating it on an aluminum foil, and vacuum drying at 120°C for 12 hours to obtain a positive electrode sheet. A metal sodium sheet is used as a negative electrode, and the spring, gasket, negative electrode, diaphragm, and positive electrode sheet are placed in a CR2025 button cell in the order of a spring, a gasket, a negative electrode, a diaphragm, and a positive electrode sheet, and an electrolyte with a concentration of 1 mol / L is added with sodium perchlorate as a solute, polycarbonate and ethylene carbonate (volume ratio of 1:1) plus 5% of fluoroethylene carbonate as a solvent, and a sodium ion button cell is obtained after packaging.
[0097] Test conditions: voltage window is 2.0~4.0V, test steps are 0.1C-0.2C-0.5C-1C-1C cycle for 100 times.
[0098] An embodiment of the present application also provides an electrical device, which includes an electrical main body and a battery, wherein the battery includes a positive electrode, and the positive electrode includes a positive electrode material prepared by the method for preparing the positive electrode material described in any one of the aforementioned embodiments, or the positive electrode includes the positive electrode material described in the aforementioned embodiments.
[0099] Furthermore, the positive electrode material and preparation method thereof, positive electrode plate, battery and power-consuming device of the present application coat the polyanion system external coating material on the surface of the layered oxide internal core material; the polyanion system external coating material belongs to metal phosphate, and it can enhance the ion transport characteristics by coating the layered oxide internal core material as a coating layer. The polyanion system external coating material increases ion diffusion by forming a double-layer structure with the layered oxide internal core material, reduces the dissolution of manganese and reduces the Jahn-Teller effect, improves its disadvantage of poor environmental stability, and improves cycle performance. Compared with traditional coating materials (such as nano-metal oxides and carbon materials), the polyanion-based external coating material itself is an active substance with a certain specific capacity, and will not reduce the energy density of the positive electrode material too much; at the same time, compared with general polyanion-based materials (such as sodium ferric pyrophosphate), sodium manganese ferric pyrophosphate is doped with manganese, which improves the voltage platform of the polyanion-based external coating material and improves the disadvantage of the low voltage platform of the polyanion-based material, making the voltage platform of the polyanion-based external coating material closer to the internal core material of the coated layered oxide, which helps to improve the overall voltage platform of the positive electrode material.
[0100] Example 1
[0101] Step 1: 300g of chemical formula Ni 0.33 Fe 0.34 Mn 0.33 The nickel iron manganese precursor (OH)2 was mixed with 177.65g of sodium bicarbonate with a purity of 99.5% in a blender at high speed for 15 minutes, and then heated to 1000°C at a heating rate of 3°C / min in a tubular furnace. After sintering for 10 hours, it was naturally cooled. Dry air was used as the sintering atmosphere. The sintered product was crushed by a wall breaker and sieved with a 150-mesh sieve to obtain a single-crystalline sodium nickel iron manganese layered oxide positive electrode material, recorded as NFM-1.
[0102] Step 2: Weigh 200g of FePO4, 148.52g of NaHCO3, 50.85g of NH4H2PO4, and 19.2g of citric acid, mix and stir in 1000ml of pure water for 15 minutes to obtain a precursor slurry. Place the container containing the solution on a resistance furnace, insert an ultrasonic probe and turn on the ultrasound, the solution boils, evaporates, concentrates, and burns to obtain a fluffy precursor powder. The obtained precursor dry powder is loaded into an alumina sagger and sintered in a kiln. The sintering atmosphere is nitrogen. The sintering system is set to two stages of sintering. The first stage is pre-sintering, set at 300℃ and 6 hours, and the second stage is sintering, set at 550℃ and 10 hours. Finally, it is cooled naturally. After sintering, it is crushed using a wall breaker, and then sieved using a 150-mesh screen to obtain the finished product, recorded as NFPP-1.
[0103] Step 3: Weigh 95 g of NFM-1 and 5 g of NFPP-1, put them into a mechanical fusion machine, set the speed to 5000 rpm, and mix at high speed for 3 minutes to obtain the final product, which is recorded as NFM / NFPP-1.
[0104] Example 2
[0105] Compared with Example 1, Example 2 only changes the ratio of the two materials used in the coating mixture.
[0106] Step 1 and step 2 are exactly the same as those in Example 1 and will not be further explained.
[0107] Step 3: Weigh 90g of NFM-1 and 10g of NFPP-1, put them into a mechanical fusion machine, set the speed to 5000rpm, and mix at high speed for 3 minutes to obtain the final product, which is recorded as NFM / NFPP-2.
[0108] Example 3
[0109] Compared with Example 1, Example 3 only changes the ratio of the two materials used in the coating mixture.
[0110] Step 1 and step 2 are exactly the same as those in Example 1 and will not be further explained.
[0111] Step 3: Weigh 85g of NFM-1 and 15g of NFPP-1, put them into a mechanical fusion machine, set the speed to 5000rpm, and mix at high speed for 3 minutes to obtain the final product, which is recorded as NFM / NFPP-3.
[0112] Comparative Example 1
[0113] Step 1: Completely the same as in Example 1.
[0114] Step 2: Weigh 200g of FePO4, 148.52g of NaHCO3, 50.85g of NH4H2PO4, and 19.2g of glucose, mix and stir in 1000ml of pure water for 15 minutes to obtain a precursor slurry; grind the obtained precursor slurry in a sand mill, use 0.2mm zirconium oxide zirconium beads, set the grinding speed to 1200rpm, grind for 90 minutes, the particle size D50 = 247nm, and the viscosity is 17800. The ground slurry is dried using a centrifugal atomizer spray dryer, the speed is set to 25000rpm, the inlet air temperature is 260℃, and the outlet air temperature is controlled at 105℃±5℃ to obtain a precursor dry powder. The obtained precursor dry powder was loaded into an alumina sagger and sintered in a kiln. The sintering atmosphere was nitrogen and the sintering system was set to two stages. The first stage was pre-sintering at 300°C and 6 hours, and the second stage was sintering at 550°C and 10 hours. Finally, it was naturally cooled. After sintering, it was crushed with a wall breaker and then sieved with a 150-mesh sieve to obtain the finished product, recorded as NFPP-2.
[0115] Step 3: Weigh 95 g of NFM-1 and 5 g of NFPP-2, put them into a mechanical fusion machine, set the speed to 5000 rpm, and mix at high speed for 3 minutes to obtain the final product, which is recorded as NFM / NFPP-4.
[0116] Comparative Example 2
[0117] Compared with Example 1, Comparative Example 2 changed the method of coating and mixing two materials.
[0118] Step 1 and step 2 are exactly the same as those in Example 1 and will not be further explained.
[0119] Step 3: Weigh 95g of NFM-1 and 5g of NFPP-1, add 100ml of NMP solvent, mix in a planetary ball mill, set the speed to 400rpm, and mix for 30 minutes. After mixing, dry in an electric vacuum oven, set the oven temperature to 120°C. After drying for 6 hours, use a wall breaker to crush the dried material to obtain the final product, recorded as NFM / NFPP-5.
[0120] Comparative Example 3
[0121] Compared with Example 1, Comparative Example 3 changes the method of coating and mixing two materials.
[0122] Step 1 and step 2 are exactly the same as those in Example 1 and will not be further explained.
[0123] Step 3: Weigh 95 g of NFM-1 and 5 g of NFPP-1, use a wall breaker to crush and mix them to obtain the final product, recorded as NFM / NFPP-6.
[0124] Comparative Example 4
[0125] Compared with Example 1, Comparative Example 4 adjusted the setting parameters and operating time of the mechanical fusion machine.
[0126] Step 1 and step 2 are exactly the same as those in Example 1 and will not be further explained.
[0127] Step 3: Weigh 95 g of NFM-1 and 5 g of NFPP-1, put them into a mechanical fusion machine, set the speed to 1000 rpm, and mix at high speed for 1 minute to obtain the final product, which is recorded as NFM / NFPP-7.
[0128] Comparative Example 5
[0129] Compared with Comparative Example 4, Comparative Example 5 adjusts the operating time of the mechanical fusion machine.
[0130] Step 1 and step 2 are exactly the same as those in Example 1 and will not be further explained.
[0131] Step 3: Weigh 95 g of NFM-1 and 5 g of NFPP-1, put them into a mechanical fusion machine, set the speed to 1000 rpm, and mix at high speed for 3 minutes to obtain the final product, which is recorded as NFM / NFPP-8.
[0132] Comparative Example 6
[0133] Compared with Comparative Example 4, Comparative Example 6 adjusts the operating time of the mechanical fusion machine.
[0134] Step 1 and step 2 are exactly the same as those in Example 1 and will not be further explained.
[0135] Step 3: Weigh 95 g of NFM-1 and 5 g of NFPP-1, put them into a mechanical fusion machine, set the speed to 1000 rpm, and mix at high speed for 10 minutes to obtain the final product, which is recorded as NFM / NFPP-9.
[0136] Comparative Example 7
[0137] Compared with Example 1, Comparative Example 7 adjusted the setting parameters and operating time of the mechanical fusion machine.
[0138] Step 1 and step 2 are exactly the same as those in Example 1 and will not be further explained.
[0139] Step 3: Weigh 95 g of NFM-1 and 5 g of NFPP-1, put them into a mechanical fusion machine, set the speed to 3000 rpm, and mix at high speed for 1 minute to obtain the final product, which is recorded as NFM / NFPP-10.
[0140] Comparative Example 8
[0141] Compared with Comparative Example 7, Comparative Example 8 adjusts the operating time of the mechanical fusion machine.
[0142] Step 1 and step 2 are exactly the same as those in Example 1 and will not be further explained.
[0143] Step 3: Weigh 95 g of NFM-1 and 5 g of NFPP-1, put them into a mechanical fusion machine, set the speed to 3000 rpm, and mix at high speed for 3 minutes to obtain the final product, which is recorded as NFM / NFPP-11.
[0144] Comparative Example 9
[0145] Compared with Comparative Example 7, Comparative Example 9 adjusts the operating time of the mechanical fusion machine.
[0146] Step 1 and step 2 are exactly the same as those in Example 1 and will not be further explained.
[0147] Step 3: Weigh 95 g of NFM-1 and 5 g of NFPP-1, put them into a mechanical fusion machine, set the speed to 3000 rpm, and mix at high speed for 10 minutes to obtain the final product, which is recorded as NFM / NFPP-12.
[0148] Comparative Example 10
[0149] Compared with Example 1, Comparative Example 10 adjusted the operating time of the mechanical fusion machine.
[0150] Step 1 and step 2 are exactly the same as those in Example 1 and will not be further explained.
[0151] Step 3: Weigh 95 g of NFM-1 and 5 g of NFPP-1, put them into a mechanical fusion machine, set the speed to 5000 rpm, and mix at high speed for 1 minute to obtain the final product, which is recorded as NFM / NFPP-13.
[0152] Comparative Example 11
[0153] Compared with Example 1, Comparative Example 11 adjusted the operating time of the mechanical fusion machine.
[0154] Step 1 and step 2 are exactly the same as those in Example 1 and will not be further explained.
[0155] Step 3: Weigh 95 g of NFM-1 and 5 g of NFPP-1, put them into a mechanical fusion machine, set the speed to 5000 rpm, and mix at high speed for 10 minutes to obtain the final product, which is recorded as NFM / NFPP-14.
[0156] like Figures 1 to 6As shown, it can be seen from the electron microscope image that, compared with Example 1, in the material NFM / NFPP-6 prepared in Comparative Example 3, the two materials are simply mixed together, and the polyanion positive electrode material is not coated on the surface of the layered oxide, while the NFM / NFPP-5 material prepared in Comparative Example 2 is coated, but not uniformly.
[0157] The first-cycle specific capacity and cycle capacity retention rate under different polyanion material coating ratios were compared, and it was found that the larger the coating amount, the higher the cycle capacity retention rate, but the capacity decreased with the increase of the ratio.
[0158] Regarding the performance comparison under different mechanical fusion machine equipment parameters, the first cycle specific capacity of the material at 1000rpm and 3000rpm is not much different from that at 5000rpm. After 100 cycles, the capacity retention rate is lower than that at 5000rpm. For different mixing times, the capacity retention rate of 100 cycles is lower than that of 3 minutes at 1 minute mixing time, and the capacity retention rate is not much different at 10 minutes mixing time. It can be seen that 5000rpm mixing for 3 minutes is a better choice for mechanical fusion machine parameters.
[0159] Table 1 below is a comparison of the cycle data corresponding to the products of Examples 1 to 3 and Comparative Examples 1 to 11.
[0160] Table 1
[0161] serial number Mixing ratio rpm time 100C cycle capacity Capacity retention rate NFM / NFPP-1 95:5 5000 3min 125.96 96.37% NFM / NFPP-2 90:10 5000 3min 122.07 97.41% NFM / NFPP-3 85:15 5000 3min 116.42 98.57% NFM / NFPP-4 95:5 5000 3min 118.74 90.84% NFM / NFPP-5 95:5 / / 106.54 76.59% NFM / NFPP-6 95:5 / / 84.57 60.84% NFM / NFPP-7 95:5 1000 1min 99.72 76.30% NFM / NFPP-8 95:5 1000 3min 105.24 80.52% NFM / NFPP-9 95:5 1000 10min 104.48 79.94% NFM / NFPP-10 95:5 3000 1min 106.52 81.50% NFM / NFPP-11 95:5 3000 3min 117.48 89.89% NFM / NFPP-12 95:5 3000 10min 118.24 90.47% NFM / NFPP-13 95:5 5000 1min 116.54 89.17% NFM / NFPP-14 95:5 5000 10min 125.47 96.00%
[0162] The present invention synthesizes the layered oxide internal core material and the polyanion system external coating material of the composite sodium positive electrode material by high temperature solid phase method and solution combustion method respectively. The difference from the prior art is that:
[0163] When synthesizing the polyanion sodium electric material for the coating layer, the present application selected sodium ferromanganese pyrophosphate. Compared with other coating materials, this material has the advantages of high specific capacity and high voltage platform. For the selection of the synthesis process, the solution combustion method plus ultrasound was selected. The material prepared by this synthesis method is fluffy and porous, with a high specific surface area, which is more conducive to the coating of the material.
[0164] This application uses mechanical fusion as a physical method, which does not involve chemical reactions such as sintering, and will not produce side reactions to generate impurities. Through high-speed stirring, the high-speed motion and collision of zirconium balls are used to break the secondary particles of the polyanion material used for coating into nano-scale primary particles, making the coating denser. This method is a dry coating. Compared with traditional wet coating, the intermolecular forces between the two materials of the core and the coating are smaller, easier to combine, and the process is simple and the cost is lower, which is conducive to industrialization. However, during the experiment, the mixing time was long, resulting in a high material temperature. Therefore, a mechanical fusion equipment tank with temperature control and cooling water interlayer was selected to shorten the single fusion time to prevent the material temperature from being too high.
[0165] This application uses a mechanical fusion method to composite two different systems of sodium ion battery cathode materials. Without substantially affecting the energy density of the layered oxide cathode, the polyanion system material with good stability is coated on the surface of the layered oxide material to reduce the surface residual alkali, inhibit its reaction with moisture in the air, and effectively improve its cycle performance. The composite material has stable performance and has the advantages of high energy density and good cycle performance of the two systems of cathode materials. In addition, this method does not require secondary sintering after mixing, has low cost, and is suitable for industrialization.
[0166] In the above, the specific embodiments of the present application are described with reference to the accompanying drawings. However, those skilled in the art will appreciate that various changes and substitutions may be made to the specific embodiments of the present application without departing from the scope of the present application. These changes and substitutions are all within the scope defined by the present application.
Claims
1. A method for preparing a positive electrode material, characterized in that: The steps include: preparing a layered oxide internal core material, wherein the layered oxide internal core material is a layered oxide containing sodium and a transition metal; preparing a polyanion system external coating material, wherein the polyanion system external coating material comprises sodium manganese ferrophosphate pyrophosphate; The inner core material of the layered oxide and the outer coating material of the polyanion system are fused by mechanical fusion to obtain a positive electrode material having a core-shell structure of a composite of the layered oxide and the polyanion.
2. The method for preparing the positive electrode material according to claim 1, characterized in that: The steps of preparing the layered oxide internal core material include: A certain amount of sodium source is added to the metal hydroxide precursor, mixed evenly and then sintered; The sintered material is crushed and sieved to obtain the layered oxide internal core material.
3. The method for preparing the positive electrode material according to claim 2, characterized in that: The chemical formula of the metal hydroxide precursor is M(OH)2, wherein M includes at least one of Fe, Ni, Cu, Zn, Co, Ti, and Mn, the sodium source includes one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, and sodium acetate, the molar ratio of the Na element to M in the metal hydroxide precursor is 1.2:1 to 0.8:1, the sintering temperature ranges from 800°C to 1200°C, and the sintering time is 10 hours to 20 hours.
4. The method for preparing the positive electrode material according to claim 1, characterized in that: The steps of preparing the polyanion system external coating material include: Mixing an iron source, a sodium source, a phosphorus source, a carbon source, and citric acid in a solvent to form a solution; The solution is placed in a resistance furnace for heating, the temperature range of the resistance furnace is 200° C. to 600° C., and ultrasound of 20 kHz to 100 kHz is applied to the solution to make the solution boil, evaporate, condense and burn, so as to obtain a precursor powder; The precursor powder is sintered in an inert gas atmosphere, and then pulverized to obtain the polyanion-based external coating material.
5. The method for preparing the positive electrode material according to claim 4, characterized in that: The iron source includes one or more of ferrous oxalate, ferric nitrate, and ferric sulfate; the phosphorus source includes one or more of ferric phosphate, ammonium dihydrogen phosphate, sodium phosphate, sodium dihydrogen phosphate, phosphoric acid, sodium pyrophosphate, sodium dihydrogen pyrophosphate, and ammonium dihydrogen pyrophosphate; the sodium source includes one or more of sodium carbonate, sodium hydroxide, sodium bicarbonate, sodium dihydrogen phosphate, sodium acetate, and sodium oxalate; the carbon source includes one or more of glucose, sucrose, polyethylene glycol, citric acid, oxalic acid, carbon nanotubes, and graphite; and the solvent includes one or more of deionized water and anhydrous ethanol.
6. The method for preparing the positive electrode material according to claim 4, characterized in that: The temperature range for sintering the precursor powder is 300°C to 800°C, the sintering time for sintering the precursor powder is 6 hours to 12 hours, the inert gas includes one or more of nitrogen, helium, and argon, and the oxygen concentration is less than or equal to 20ppm; the particle size D50 of the polyanion-based external coating material ranges from 50nm to 300nm, and the specific surface area range BET of the polyanion-based external coating material is 10㎡ / g to 20㎡ / g.
7. The method for preparing the positive electrode material according to claim 1, characterized in that: The step of fusing the layered oxide inner core material and the polyanion outer coating material by mechanical fusion comprises: Weighing the layered oxide inner core material and the polyanion outer coating material to obtain a mixture, wherein the mass proportion of the polyanion outer coating material is less than or equal to 30%; The mixture is placed in a mechanical fusion machine and stirred to mix evenly. The rotation speed range of the mechanical fusion machine is 2000 rpm to 10000 rpm, and the stirring time is 3 minutes to 10 minutes. The mechanical fusion machine is equipped with zirconium balls for crushing and extruding the mixture to obtain the positive electrode material having a core-shell structure composite of layered oxides and polyanions.
8. A positive electrode material, characterized in that The positive electrode material is prepared by the method for preparing the positive electrode material according to any one of claims 1 to 7, and the positive electrode material comprises the layered oxide internal core material and the polyanion system external coating material; The layered oxide internal core material includes Na 1+x MO2, wherein -0.3≤X≤0.2, M comprises at least one of Fe, Ni, Cu, Zn, Co, Ti, and Mn; The polyanion system external coating material includes Na4Fe 3-y Mn y (PO4)2P2O7 / C.
9. A battery, characterized in that: The battery comprises a positive electrode, wherein the positive electrode comprises a positive electrode material prepared by the method for preparing a positive electrode material according to any one of claims 1 to 7, or the positive electrode comprises the positive electrode material according to claim 8.
10. An electrical device, characterized in that: The power-consuming device includes a power-consuming body and a battery, the battery includes a positive electrode, the positive electrode includes a positive electrode material prepared by the method for preparing a positive electrode material according to any one of claims 1 to 7, or the positive electrode includes the positive electrode material according to claim 8.
Citation Information
Cited By
Sodium-ion battery positive electrode material, preparation method thereof and battery
CN120895604A
NFPP nanosheet coated layered oxide positive electrode material and preparation method and application thereof
CN120895605A
Nfpp nanosheet-coated layered oxide positive electrode material and preparation method and application thereof
CN120895605B